2023
DOI: 10.3389/fpubh.2023.1073824
|View full text |Cite
|
Sign up to set email alerts
|

Obesity- and lipid-related indices as a predictor of obesity metabolic syndrome in a national cohort study

Abstract: ObjectiveMetabolic syndrome is a common condition among middle-aged and elderly people. Recent studies have reported the association between obesity- and lipid-related indices and metabolic syndrome, but whether those conditions could predict metabolic syndrome is still inconsistent in a few longitudinal studies. In our study, we aimed to predict metabolic syndrome by obesity- and lipid-related indices in middle-aged and elderly Chinese adults.MethodA national cohort study that consisted of 3,640 adults (≥45 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 87 publications
3
15
2
Order By: Relevance
“…Our study showed that a higher load of adiposity indices and lipid-related indices were associated with MetS independent of sociodemographic, behavioral, and clinical factors. This was in line with reports from the China Health and Retirement Longitudinal Study (CHARLS) survey, which showed the correlation of the higher WC, BMI, WHtR, VAI, ABSI, BRI, LAP, ConI, CVAI, TyG-index and their combined indices (TyG-BMI, TyG-WC, TyG-WHtR) with MetS in middle-aged and elderly Chinese adults [21,31]. The National Health and Nutrition Examination Survey (NHANES) study also found that lipid-related indices, such as LAP, VAI, and TyG index with MetS in older adults [18].…”
Section: /14supporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed that a higher load of adiposity indices and lipid-related indices were associated with MetS independent of sociodemographic, behavioral, and clinical factors. This was in line with reports from the China Health and Retirement Longitudinal Study (CHARLS) survey, which showed the correlation of the higher WC, BMI, WHtR, VAI, ABSI, BRI, LAP, ConI, CVAI, TyG-index and their combined indices (TyG-BMI, TyG-WC, TyG-WHtR) with MetS in middle-aged and elderly Chinese adults [21,31]. The National Health and Nutrition Examination Survey (NHANES) study also found that lipid-related indices, such as LAP, VAI, and TyG index with MetS in older adults [18].…”
Section: /14supporting
confidence: 91%
“…Especially, TyG-WHtR, as a novel lipid combined anthropometric indices, seem to be a superior indicator of MetS in the Chinese population in comparison with other anthropometric indices to screen MetS. This was consistent with the two population-based studies from Nigerians and China, which suggested TyG-related indices integrated the TyG index and anthropometric characteristics enhanced MetS identi cation and prediction [21,31,37]. Early detection of individuals at high risk for MetS remains a clinical priority, offering the potential for timely interventions that may mitigate complications and improve patient prognosis.…”
Section: /14supporting
confidence: 81%
See 1 more Smart Citation
“…TyG index provided an available approach to analyze the both of lipid metabolism and glucose status [ 16 , 17 ]. Previous studies mostly concentrate on the level of TyG index in the general population to predict the adverse outcomes of CAD and CVD [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study including 2,255 participants with IR and 7,629 participants with non-IR showed that the ratio of triglyceride-glucose to WHtR (TyG-WHtR) is a stable indicator for identifying IR and can be effectively used in clinical practice 18 . Another study conducted in China showed that among all 12 indicators related to blood lipids and obesity, the ratio of triglycerides-glucose to BMI (TyG-BMI) is the best predictor of male metabolic syndrome 19 . In addition, anthropometric parameters combined with triglycerides-glucose were better predictors of metabolic syndrome than anthropometric parameters alone.…”
Section: Discussionmentioning
confidence: 99%